FIBER OPTICS AND OPTOELECTRONICS - R P KHARE (NEW DELHI OXFORD UNIVERSITY PRESS, 2018)
Developed for beginners, the book discusses the major building blocks of fiber-optic systems and goes on to present an overview of their use in fiber-optic communication and non-communication applications of fiber optics. Its in-depth presentation supports theory with relevant examples.
Keywords: FIBER OPTICS -- OPTOELECTRONICS